VIRTUAL TEACHING SATISFACTION OF ENGLISH LECTURERS DURING PANDEMIC - Sri Supeni; Ellen Juita Gultom (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
During the pandemic, all teaching and learning processes were carried out virtually. For lecturers, teaching virtually is not an option but a necessity whether ready or not. after going on for two years, the researchers want to find out whether the lecturers who teach virtually are satisfied with the process and results of learning. Besides interviews, questionnaires were also distributed to find out how virtual learning was going. The result of the questionnaires shows that towards the teaching-process, students’ interaction is higher in online compared to face-to-face, online learning is more flexible than face-to-face learning, students are actively involved in their learning during online courses. The lecturers also think that they have a higher workload when teaching an online course as compared to the traditional one, the technical issues are also the barriers in virtual teaching in the beginning. However, after two years of virtual teaching, based on the interviews, most of the lecturers say that they are satisfied with their virtual teaching and ready for the next virtual teaching in the future.